Human and animal dietary exposure to T‐2 and HT‐2 toxin - Arcella, Davide (EFSA J, 2017)
T‐2 toxin (T2) and HT‐2 (HT2) toxin are trichothecenes, which form part of the group of Fusarium mycotoxins. Food and feed samples used to estimate human dietary and animal exposure were reported either as the individual results for T2 and/or, HT2, and/or as the sum of the two. The highest concentrations were reported in oats and oat‐containing commodities. Very high levels were reported in a small number of data on specific plant‐ and herb‐based dietary supplements. In humans, the mean chronic dietary exposure to the sum of T2 and HT2 was highest in ‘Toddlers’ and ‘Infants’, with maximum upper bound (UB) estimates of 64.8 and 62.9 ng/kg body weight (bw) per day, respectively. The 95th percentile dietary exposure was highest in ‘Infants’ with a maximum UB estimate of 146 ng/kg bw per day. UB estimations were on average fourfold higher than lower bound (LB) estimations. Average acute exposure ranged from a minimum of 13.4 ng/kg bw per day, estimated in ‘Elderly’, up to a maximum of 64.7 ng/kg bw per day estimated in ‘Toddlers’. The highest 95th percentile acute dietary exposure was estimated for a dietary survey within the age class ‘Infants’ (170 ng/kg bw per day). Overall, among processed foods the main contributors were cereal flakes, fine bakery wares and, for acute exposure, also bread and rolls. In the elderly and very elderly, dietary supplements made an important contribution. Exposure to the sum of T2 and HT2 in farm and companion animals varied according to the animal species. Exposures considering mean concentration scenarios varied between 0.03–0.08 (LB–UB) μg/kg bw per day in beef cattle and 1.13–1.47 μg/kg bw per day in milking goats. For high concentration scenarios, exposures varied between 0.12–0.16 μg/kg bw per day and 2.37–2.58μg/kg bw per day in the same species. In the absence of data, potential modified form were not included.